Restriction fragment length polymorphisms and sequence variation within the spaP gene of Streptococcus mutans serotype c isolates. - Brady, L J (1991)
A restriction fragment length polymorphism study was undertaken to determine the extent and location of heterogeneity within spaP encoding the Mr 185,000 cell surface protein P1 (antigen I/II) of Streptococcus mutans serotype c isolates. The gene was found to be highly conserved except for a central variable (V) region predicted to encode less than 150 amino acids. Sequence analysis identified two V-region variants. These differences were independent of the geographic source of the isolates. Southern analysis using synthetic oligonucleotide probes indicated that nonretention of P1 (I/II) by some isolates is not due to a deletion of the 3'-terminal DNA necessary to encode an intact carboxy terminus.